(untitled) (Journal of Sustainability, Environment and Peace, 2021)
Beach Management Units (BMUs) in Kenya were established to ensure sustainable utilization and management of the fishery resource. BMUs as co-management institutions were conceptualized after the failed state-controlled fisheries management. Sustainable management by the BMUs has however not been realized, years after the institution’s inception. The study aimed to assess the management of Migingo BMUs; establish the effects of management of BMUs on the implementation of the regulations; and assess the implementation of regulations with regards to fish stocks. The study was done in Migingo Island, Lake Victoria which borders Kenya and Uganda. Data was collected from the BMU committee members and stakeholders at the fish landing site along the island’s shores. This was done through a questionnaire based survey; semi structured interviews from key informants and; focus discussion groups. Results revealed that the three out of seven functions were performed satisfactorily by the Migingo BMU. These were revenue collection, confiscation of illegal gears and arrest of offenders, as depicted by the satisfaction of respondents at 42%, 38%, and 68%, respectively. The other functions - conducting meetings, patrol of the lake, formulation of bylaws and inventory keeping had poor performance. Migingo’s BMU structure was found to be wanting as it lacked the assembly branch. Implementation of regulations by the BMU faced various challenges; lack of support from the government, inadequate funds and equipment and inadequate knowledge to operate its functions. This study shows that BMUs are viable institutions however the poor structure and management of Migingo’s BMU along with the challenges faced in implementing the stipulated regulations led to its ineffectiveness. Capacity building is therefore needed on the BMU’s management and governance at large, provision of relevant skills, equipment and funds and improved support from the government for the BMU to be efficient and effective.